Investigating the Correlation Between Soft Skills and Career Efficacy in Students with Disabilities - Aryani, Farida; Anwar, Citra Rosalyn; Zulfitrah, Zulfitrah; Idris, Idriani; Rafli, Muhammad (Journal of Educational Science and Technology (EST), 2024)
This study aims to explore the relationship through the correlation test between soft skills and career efficacy of students with disabilities in Makassar City. This study uses a type of quantitative research with a correlational design. The participants of this study involved 50 students with disabilities spread across four universities in Makassar City (Makassar State University, Hasanuddin University, Muslim Indonesia University, Muhammadiyah Makassar University). Data collection techniques were carried out using psychological scale instruments, namely the soft skills scale of 20 statement items using a Likert scale range of 1-5 and a career efficacy scale of 32 statement items using a Likert scale range of 1-5. The instrument was first tested for content validity by experts and item validity using the Confirmatory Factor Analysis (CFA) test. This research sample technique uses purposive sampling by determining sample criteria. The results showed the results of descriptive and correlation tests that there was a relationship or correlation between soft skills variables and career confidence variables in other words, the more soft skills increase, the career confidence in Makassar City disability students.